2018
DOI: 10.1128/mspheredirect.00588-18
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Amoxicillin-Clavulanate followed by Autologous Fecal Microbiota Transplantation on Fecal Microbiome Structure and Metabolic Potential

Abstract: The spread of multidrug resistance among pathogenic organisms threatens the efficacy of antimicrobial treatment options. The human gut serves as a reservoir for many drug-resistant organisms and their resistance genes, and perturbation of the gut microbiome by antimicrobial exposure can open metabolic niches to resistant pathogens. Once established in the gut, antimicrobial-resistant bacteria can persist even after antimicrobial exposure ceases. Strategies to prevent multidrug-resistant organism (MDRO) infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 57 publications
4
14
0
Order By: Relevance
“…While bacterial taxa possessing specific resistance genes cannot yet be determined with our metagenomics sequencing platform, these data are consistent with the fact that blaTEM genes are commonly found in Proteobacteria [29], and the emergence of beta-lactam resistant E. coli has been reported in dogs treated with oral amoxicillin [30] and amoxicillin/clavulanate [31]. Similarly, in humans, amoxicillin/clavulanate exposure resulted in enrichment for beta-lactamase genes in fecal resistomes, although the bacterial species harboring these genes were not evaluated [26].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…While bacterial taxa possessing specific resistance genes cannot yet be determined with our metagenomics sequencing platform, these data are consistent with the fact that blaTEM genes are commonly found in Proteobacteria [29], and the emergence of beta-lactam resistant E. coli has been reported in dogs treated with oral amoxicillin [30] and amoxicillin/clavulanate [31]. Similarly, in humans, amoxicillin/clavulanate exposure resulted in enrichment for beta-lactamase genes in fecal resistomes, although the bacterial species harboring these genes were not evaluated [26].…”
Section: Discussionsupporting
confidence: 77%
“…However, data from the current canine study revealed that amoxicillin/clavulanate causes more alterations in gut microbiota composition than amoxicillin alone, suggesting that microbiome damage is a mechanism responsible for AAD. Amoxicillin/clavulanate is known to modify gut microbiome composition in humans [26,27], including overgrowth of Escherichia species [27], and co-administration of the probiotic, Saccharomyces boulardii, to healthy subjects with amoxicillin/clavulanate limited microbiome damage and reduced AAD rates [27]. To date, clinical analyses that directly compare gut microbiome alterations resulting from exposure to amoxicillin, amoxicillin/clavulanate, and/or amoxicillin/clavulanate formulations with differing amoxicillin/clavulanate ratios have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple case reports have described successful decolonization of MDRO Klebsiella spp., Pseudomonas, and vancomycin-resistant enterococci with allo-FMT (reviewed in [110]), though no placebo-controlled trials have yet been conducted for this express purpose. Autologous FMT has been proposed as a mechanism to restore a pre-antibiotic microbiome baseline after disruption [59,106,112]. Similarly, probiotics, strains of beneficial bacteria consumed during or after the intervention, are thought to mitigate some of the negative consequences of antibiotics on the microbiome [113][114][115].…”
Section: Therapeutics To Ameliorate Microbiome and Resistome Disruptionmentioning
confidence: 99%
“…FMT may also colonize missing flora after vancomycin exposure with priority to restore the dysbiosis. For recurrent of Clostridium difficile infection, several researchers have suggested that FMT is a superior method to oral vancomycin for the treatment [21,22], and combinations of them would be a better choice attributed to restore the intestinal microbiota [23,24]. The clinical application of FMT also includes inflammatory bowel disease, diabetes mellitus, liver cirrhosis, gut-brain disease, and others [54].…”
Section: Fmt Restored Microbiome Composition and Genesmentioning
confidence: 99%
“…Fecal microbiota transplantation (FMT) is the introduction of feces from a healthy donor into the intestinal tract of someone with disrupted microbiota, which has been confirmed superior to oral vancomycin for the treatment of Clostridium difficile infection [21,22]. And combination of FMT with vancomycin could be a better choice to treat this kind of infection [23,24]. However, there is limited information on using fecal microbiota transplantation (FMT) for restoration of intestinal microbiome affected by antibiotics.…”
mentioning
confidence: 99%